Suitability assessment of soils of Panchagarh and Thakurgaon for tea (Camellia sinensis L.) and orange (Citrus aurantium L.) cultivation - Uddin, Md Jashim; Mohiuddin, ASM; Ahmed, Shakil Uddin; Rahman, Md Khalilur; Karim, Md Abdul; Saha, Ashim Kumar (Bangladesh Journal of Botany, 2020)
Experiments were conducted in soils of the five Upazilas, namely Atwari, Tetulia, Boda, Ranisankail and Panchagarh Sadar of Panchagarh and Thakurgaon districts of Bangladesh to assess their potentialities for tea and orange cultivation. Geographic Information Systems (GIS) based soil suitability map was prepared depending on the hydrological, land and soil characteristics. It was observed that about 86, 76 and 50% soils in Atwari, Tetulia and Panchagarh Sadar Upazilas, respectively are suitable for tea and orange cultivation. But in Boda and Ranisankail Upazilas above 60% soils are suitable for cultivation of tea and orange. Besides, five representative soil pedons, namely Bhajanpur, Ranisankail, Pirgachha, Domar and Dimla were studied and compared with the standard suitability formats. The results revealed that soils of the Thakurgaon and Panchagarh districts under the Old Himalayan piedmont plain are suitable for tea and orange cultivation. There is a vast scope of utilizing the land and soil resources of the above sites for tea and orange farming.